Primo Levi: the articulator of memories - Mauro, Claudia Fernanda de Campos[UNESP] (2022)
This article establishes the poetic and aesthetic steps of the articulation of memory in the work Is this a man?, by the Italian author Primo Levi. In the work, Levi seeks to establish mnemonic paths to, through the memory of his period as a prisoner of the concentration camp in Auschwitz, denounce the atrocities of the German extermination factory against Jews, in World War II, through the eternalization of his testimony in a work poetic. Through his outrage at the horror, Levi narrates the engineering of Nazi death, to show that the Holocaust was a complex system of human execution through a painstaking process of dehumanization and deconstruction of all traces of dignity of prisoners in camps. of concentration.